A Three-Dimensional Conceptual Framework of Corporate Water Responsibility. (June 2015) - Martinez, Fabien
This article offers a conceptual framework that comprehensively describes essential aspects of corporate water responsibility. What heretofore has been essentially regarded as an issue to be tackled by governmental institutions, and therefore not perceived as an important component of the value that is created for the institutional and private owners of profit-driven companies, is explicitly treated here as a corporate responsibility. Bridging knowledge domains, I review major research works conducted by management, corporate sustainability, and (welfare) economics scholars and focusing on water management issues to unveil the conditions under which corporations are likely to manage, or to be challenged in managing, water in responsible/sustainable ways. Three types of "tensions" that confront academics and managers alike are discussed: voluntary actions versus coercion, free riding versus cooperation, and economic versus corporate water responsibility motives. I propose a three-dimensional framework of corporate water responsibility for thinking through the managerial response patterns contemplated to address these tensions.